2015
DOI: 10.3171/2014.11.jns14804
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin is associated with an increased risk of subdural hematoma in normal-pressure hydrocephalus patients following shunt implantation

Abstract: obJect In this paper the authors investigate whether shunt-treated patients with normal-pressure hydrocephalus receiving aspirin therapy are at increased risk of developing subdural hematoma (SDH). Methods Records from 80 consecutive patients who had undergone implantation of a cerebrospinal fluid shunt for the treatment of normal-pressure hydrocephalus were retrospectively reviewed. results Eleven cases of symptomatic SDH occurred, all among patients receiving aspirin or clopidogrel. The 5-year survival estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 12 publications
2
5
0
1
Order By: Relevance
“…A recent report found a significantly increased rate of SDH among NPH patients who were using aspirin and underwent a VPS. [2] On the other hand, the chronic use of warfarin was found to be safe in a series of 15 NPH patients who underwent VPS insertion, as the rate of SDH was not higher than in other reports. [7]…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…A recent report found a significantly increased rate of SDH among NPH patients who were using aspirin and underwent a VPS. [2] On the other hand, the chronic use of warfarin was found to be safe in a series of 15 NPH patients who underwent VPS insertion, as the rate of SDH was not higher than in other reports. [7]…”
Section: Discussionmentioning
confidence: 87%
“…[4914] Cerebrospinal fluid (CSF) shunting is considered a risk factor for subdural hematomas (SDH), which may develop among 2–17% of patients with CSF shunts. [2715] It is thought that the decrease in size of the drained ventricles results in stretching of bridging veins in the subdural space, making them prone for bleeding following even minor traumas. Additionally, a shunt can decrease the size of the ventricles, allowing more space for the developing hematoma while avoiding a potential “tamponade” effect, thus creating a more favorable milieu for bleeds to expand.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 A study of patients with NPH who received ASA therapy and were treated with a VP shunt showed a significant increase of the occurrence of cSDH associated with antithrombotic therapy compared with nonusers. 2 Those authors proposed withholding ASA treatment 7 days prior to surgery and resuming it on the 1st-2nd postoperative day. However, it was shown that the antithrombotic effect of ASA vanishes in half of the patients after 72 hours and in 80% of the cases after 96 hours.…”
Section: Association Between Asa Therapy and Bleeding Events After Vpmentioning
confidence: 99%
“…Ликворошунтирующие операции и даже просто вентрикулостомия, которые, казалось бы, вполне можно отнести к хирургии «малого риска кровотечения», оказывается, тоже сопровождаются, согласно данным литературы [14,[30][31][32][33][34][35], достаточно высоким процентом геморрагических осложнений, в особенности на фоне проводимой ДАТ -ситуации, весьма похожей на описанную в нашем случае, а использование «мостиковой» терапии низкомолекулярными гепаринами или нефракционированным гепарином оказалось малоэффективным в профилактике тромбоза коронарного стента.…”
Section: рис 3 внешний вид больного ш после операцииunclassified